The Failure of Education as an Economic Strategy - Thurow, Lester C. (American Economic Review, 1982)
Arthur Okun wrote Equality And Efficiency: The Big Tradeoff in 1974. The book focused on the tradeoffs between tax-transfer systems and the work or savings incentives necessary for economic growth. If society wished more equality it faced a leaky bucket where the amount given to the poor was inevitably less than the amount taken from the rich. If the book had been written ten years earlier, Okun would not have focused on the big tradeoff. The conventional wisdom (circa 1964) held that any society could have both more output and a more equal distribution of output if only it invested in more education-human capital. If a more equal distribution of education was pumped into the economy, the economy would automatically pump back a more equal distribution of earnings. As educational gaps diminished between blacks and whites, or men and women, earnings gaps would similarly disappear. The War on Poverty and Great Society programs as they were conceived by Presidents Kennedy and Johnson were based upon education-not tax-transfer-strategies. With more education, higher earnings for the poor would mean higher, not lower, incomes for the rich. Strangely, Equality and Efficiency says nothing about education. The only reference to education is a brief discussion of the Yale Plan where tuition loans could be repaid based on future earnings rather than some fixed repayment schedule. Nowhere in the book does Okun justify his association of equality with the tax-transfer system on the grounds that education empirically failed to deliver what was earhler promised. Without argument he just assumes that the tax-transfer system is the only way to get a more equal distribution of income. Between the mid-1960's and the mid-1970's, I am unaware of anyone who was advancing the argument that education had empirically failed as an economic strategy for generating both growth and equality. Yet Okun was not alone in ignoring education. Without explicit discussion, education had ceased to be seen as a viable economic strategy by almost everyone. Intellectually it is interesting to speculate as to why equality, which was so closely associated with education in 1960's, came to be just as closely associated with tax-transfer systems in the 1970's without any hard analysis that would have forced the shift in strategy. Perhaps it had something to do with the public's disgust with education flowing out of the student rebellion of the late 1960's and early 1970's. More education was not a politically viable strategy for promoting equality and efficiency whatever its economic merits. But more importantly, the evidence, at least on the surface, now indicates that the educational strategy of the 1960's did fail economically. The educational attainments of the labor force continued to accelerate in the 1970's, but productivity stopped growing by the end of the decade. (See the Economic Report of the President, 1981.) There is no educational gap between men and women who work at year-round full-time jobs (both have 12.0 median years of education in 1978), but women continue to earn 58 percent of what men earn. (See Current Population Reports... 1978, No. 123, pp. 213; 218.) Education has been much more equally distributed since World War II, but the earnings of the top quintile rose from 19 times that of the bottom quintile in 1948 to 27 times that of the bottom quintile in 1980 (Current Population Reports... 1968, No. 6, p. 28; No. 123, p. 271). Why didn't education deliver the growth and rising equality that was promised? One can quickly think of many reasons why education may appear to be failing as a strategy for promoting growth and equality *Massachusetts Institute of Technology.